Potential of antibacterial compound from extract of the green algae Bornetella sp. Issue 1 (July 2021) - Bahrun,; Soekamto, N H; Firdaus,; Akbar, A
Abstract: Antibiotics resistance has become an obstacle in the treatment of various types of diseases caused by bacterial infections. The investigation of secondary metabolites from macroalgae as antibiotic reference compounds can be done as an effort to overcome this problem. Potential test for antibacterial compounds from green algae Bornetellasp has been carried out against Escherecia coli and Staphylococcus aureus bacteria. The secondary metabolite extraction process was carried out using a multilevel maceration method using n-hexane, chloroform, ethyl acetate and methanol as solvents. The extract obtained was then tested for phytochemicals and their activity against the tested bacteria by the paper disc diffusion method. The test results obtained showed that the chloroform extract had the highest activity with an inhibition zone diameter of 16.33 ±1.18 mm against E. coli and 14.26 ±0.69 mm against S. aureus . The presence of secondary metabolites of the alkaloid, steroid, phenolic and flavonoid groups based on the results of phytochemical screening is the cause of this activity.